2002
DOI: 10.1159/000059374
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Antibiotic Treatment on the Concentrations of Interleukin-6 and Interleukin-8 in Cervicovaginal Fluid

Abstract: Objective: We investigated to see the effect of antibiotics on interleukin (IL)-6 and IL-8 in cervicovaginal fluid in patients with premature rupture of the membranes. Study Design: Cervicovaginal fluid was sampled on admission and before delivery for measurement of IL-6 and IL-8 from 31 patients with less than 35 weeks of gestation. Concentrations of IL-6 and IL-8 were measured by ELISA. Results: The concentrations of IL-6 in cervicovaginal fluid in patients who were delivered because of clinical chorioamnion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Production of chemokines and cytokines by uterine epithelial cells may contribute to pathological conditions during pregnancy. A correlation between elevated concentrations of IL‐6, IL‐8 and MCP‐1 and amniotic microbial infection has been found in cervicovaginal fluid and amniotic fluids from patients in preterm labor and premature rupture of membranes (69–71). Although some of these factors participate in normal parturition (72), levels were excessive in women with infection.…”
Section: Epithelial Cells In the Frt: Enablers And Conduits Of Innatementioning
confidence: 99%
“…Production of chemokines and cytokines by uterine epithelial cells may contribute to pathological conditions during pregnancy. A correlation between elevated concentrations of IL‐6, IL‐8 and MCP‐1 and amniotic microbial infection has been found in cervicovaginal fluid and amniotic fluids from patients in preterm labor and premature rupture of membranes (69–71). Although some of these factors participate in normal parturition (72), levels were excessive in women with infection.…”
Section: Epithelial Cells In the Frt: Enablers And Conduits Of Innatementioning
confidence: 99%
“…In the setting of preterm premature rupture of membranes, cervical IL-6 levels have been found to be elevated in patients with intra-amniotic infection 16,17 and in those who delivered within 7 days. 16 In the setting of preterm labor with intact membranes, intra-amniotic infection has been associated with elevated cervical levels of IL-6, IL-1β, IL-1RA, tumor necrosis factor-α, 18 IL-8, 19 and insulin-like growth factor binding protein 1. 20 Vaginal IL-8 levels have been found to be elevated in both term and preterm labor and to correlate with cervical dilation 21 and the presence of intra-amniotic infection.…”
Section: Partial Human Vaginal Fluid Proteomementioning
confidence: 99%
“…A correlation between elevated concentrations of IL-6, IL-8, and MCP-1 and amniotic microbial infection has been found in cervicovaginal fluid and amniotic fluids from patients in preterm labor and premature rupture of membranes. [132][133][134] Romero and colleagues reported on the association between bacterial vaginosis and preterm birth and demonstrated compelling evidence for TNFα in preterm parturition associated with infection. 135 Simhan and colleagues found that low cervical fluid concentrations of IL-1β, IL-8, and IL-6 correlated with clinical chorioamnionitis in early pregnancy.…”
Section: Role Of Uterine Epithelial Cells In Immune Protection Backgrmentioning
confidence: 99%